Mathematics physics learning e-module: Differences in perceptions and interests based on gender - Astalini Astalini; Darmaji Darmaji; Haerul Pathoni; Dwi Agus Kurniawan; Riska Fitriani (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2021)
This study aims to find out the differences in perception and interest of physics education students of FKIP Jambi University towards e-module Mathematics Physics reviewed based on gender differences. This research uses a type of quantitative research, namely survey research. The instrument that has been used is the perception questionnaire. Furthermore, the data obtained is analyzed using descriptive statistics, and inferential statistics, namely assumption tests (normality tests and homogeneity tests) and hypothesis tests (one-way ANOVA tests) with Scheffe advanced tests. The instrument that has been used is the perception questionnaire. Furthermore, the data obtained is analyzed using descriptive statistics, and inferential statistics, namely assumption tests (normality tests and homogeneity tests) and hypothesis tests (one-way ANOVA tests) with Scheffe advanced tests. Sampling is done using the total sampling technique because the number of samples used is equal to the population of 91 students of physics education at FKIP Jambi University. Sampling is done using the total sampling technique because the number of samples used is equal to the population of 91 students of physics education at FKIP Jambi University. The results of this study are differences in students' perceptions and interests of the Mathematics Physics e-module, namely the average student's perception of the Mathematics Physics e-module, which women in class B best own, and the average student's interest in the Mathematics e-module. The female in class B also owns the best physics.